The Effect of the No Pain Labor & Delivery-Global Health Initiative on Cesarean Delivery and Neonatal Outcomes in China: An Interrupted Time-Series Analysis. (22nd April 2020) - Drzymalski, Dan M.; Guo, Jun-Cai; Qi, Xue-Qin; Tsen, Lawrence C.; Sun, Yingyong; Ouanes, Jean-Pierre P.; Xia, Yun; Gao, Wei Dong; Ruthazer, Robin; Hu, Fengling; Hu, Ling-Qun
Abstract : BACKGROUND: The proportion of live births by cesarean delivery (CD) in China is significant, with some, particularly rural, provinces reporting up to 62.5%. The No Pain Labor & Delivery-Global Health Initiative (NPLD-GHI) was established to improve obstetric and neonatal outcomes in China, including through a reduction of CD through educational efforts. The purpose of this study was to determine whether a reduction in CD at a rural Chinese hospital occurred after NPLD-GHI. We hypothesized that a reduction in CD trend would be observed. METHODS: The NPLD-GHI program visited the Weixian Renmin Hospital, Hebei Province, China, from June 15 to 21, 2014. The educational intervention included problem-based learning, bedside teaching, simulation drill training, and multidisciplinary debriefings. An interrupted time-series analysis using segmented logistic regression models was performed on data collected between June 1, 2013 and May 31, 2015 to assess whether the level and/or trend over time in the proportion of CD births would decline after the program intervention. The primary outcome was monthly proportion of CD births. Secondary outcomes included neonatal intensive care unit (NICU) admissions and extended NICU length of stay, neonatal antibiotic and intubation use, and labor epidural analgesia use. RESULTS: Following NPLD-GHI, there was a level decrease in CD with an estimated odds ratio (95% confidence interval [CI]) of 0.87 (0.78–0.98), P = .017, with odds (95% CI) of monthly CD reduction an estimated 3% (1–5; P < .001), more in the post- versus preintervention periods. For labor epidural analgesia, there was a level increase (estimated odds ratio [95% CI] of 1.76 [1.48–2.09]; P < .001) and a slope decrease (estimated odds ratio [95% CI] of 0.94 [0.92–0.97]; P < .001). NICU admissions did not have a level change (estimated odds ratio [95% CI] of 0.99 [0.87–1.12]; P = .835), but the odds (95% CI) of monthly reduction in NICU admission was estimated 9% (7–11; P < .001), greater in post- versus preintervention. Neonatal intubation level and slope changes were not statistically significant. For neonatal antibiotic administration, while the level change was not statistically significant, there was a decrease in the slope with an odds (95% CI) of monthly reduction estimated 6% (3–9; P < .001), greater post- versus preintervention. CONCLUSIONS: In a large, rural Chinese hospital, live births by CD were lower following NPLD-GHI and associated with increased use of labor epidural analgesia. We also found decreasing NICU admissions. International-based educational programs can significantly alter practices associated with maternal and neonatal outcomes.